(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The current research is to evaluate under this scenario the financial performance of Punjab National Bank, India’s second largest government bank. The study revealed that the Bank selected performed correctly with the sources of growth and financial efficiency, however the position of profitability throughout the study period was determined to be bad. The financial sector is one of the sections of the economy which has attracted considerable attention in recent years. In the vast range of the financial industry, scholars and policymakers focused on the banking sector. Concerns about financial stability that are a major political issue for central banks around the globe are increasingly recognized as a critical precondition for speedy and inclusive growth in fostering strong financial institutions, notably banks. Banking is one of the key contributors to a country’s economic growth. It serves for all economic activity as the key conduit. The post-independence banking sector in India has experienced significant transformations.